2011
DOI: 10.1111/j.1466-8238.2011.00691.x
|View full text |Cite
|
Sign up to set email alerts
|

Historic and recent fragmentation coupled with altitude affect the genetic population structure of one of the world's highest tropical tree line species

Abstract: Aim  To assess the effects of altitude and historic and recent forest fragmentation on the genetic diversity and structure of the wind‐pollinated tropical tree line species Polylepis incana. Location  One of the highest mountain forest regions of the world, located in the Eastern Cordillera of the Ecuadorian Andes. Methods  We compared genetic diversity and structure of adult trees with those of seedlings (n= 118 in both cases) in nine forest stands spanning an altitudinal gradient from 3500 to 4100 m a.s.l. u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
6
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 49 publications
2
49
6
6
Order By: Relevance
“…Average heterozygosity for P. multijuga (He = 0.12-0.14) was lower than reported for other species with similar life histories and measured using dominant markers (He = 0.25-0.27) (Nybom 2004). These values are very similar to those obtained in a study of P. incana (He = 0.13-0.17) that also has a fairly restricted range from Ecuador to Peru and is currently classified as vulnerable (Hensen et al 2011). The low genetic diversity found in these endemic species is predicted to increase inbreeding and decrease their ability to adapt to environmental change (Frankham et al 2010).…”
Section: Genetic Differentiation Among Fragmentssupporting
confidence: 83%
See 2 more Smart Citations
“…Average heterozygosity for P. multijuga (He = 0.12-0.14) was lower than reported for other species with similar life histories and measured using dominant markers (He = 0.25-0.27) (Nybom 2004). These values are very similar to those obtained in a study of P. incana (He = 0.13-0.17) that also has a fairly restricted range from Ecuador to Peru and is currently classified as vulnerable (Hensen et al 2011). The low genetic diversity found in these endemic species is predicted to increase inbreeding and decrease their ability to adapt to environmental change (Frankham et al 2010).…”
Section: Genetic Differentiation Among Fragmentssupporting
confidence: 83%
“…TDR was relatively protected from grazing since it was located in a deep ravine. The level of differentiation (PhiPT = 0.135) found for adults in this study is less than half that reported for adult and seedling P. incana (PhiPT = 0.307, 0.298, respectively) (Hensen et al 2011). The high level of differentiation found for P. incana, which is also a wind pollinated tree, suggests that historical fragmentation operating on the scale of hundreds of years has decreased gene flow in this species (Hensen et al 2011).…”
Section: Genetic Differentiation Among Fragmentsmentioning
confidence: 53%
See 1 more Smart Citation
“…Como con la mayoría de las especies de árboles tropicales, la fragmentación de los bosques de Polylepis disminuyen significativamente la diversidad genética de las poblaciones a pesar de ser polinizada por el viento, que a menudo muestran una menor pérdida genética de la fragmentación (Hensen et al 2012). Además, las poblaciones en las elevaciones más altas tienen menor diversidad genética que otras poblaciones (Aragundi et al 2011, Hensen et al 2012) y se ha encontrado que la diversidad genética en P. multijuga era aproximadamente la mitad que otro especies polinizadas por el viento (Quinteros-Casaverde et al 2012). Esto es posiblemente la resulta de los cuellos de botella genéticos y efectos fundadores durante las migraciones de ladera del Holoceno o la corta duración de la temporada de cultivo y temperaturas más frías en las elevaciones más altas (Hensen et al 2012).…”
Section: Otra Posibilidad Para Muchas Poblaciones Disyuntas Deunclassified
“…Además, las poblaciones en las elevaciones más altas tienen menor diversidad genética que otras poblaciones (Aragundi et al 2011, Hensen et al 2012) y se ha encontrado que la diversidad genética en P. multijuga era aproximadamente la mitad que otro especies polinizadas por el viento (Quinteros-Casaverde et al 2012). Esto es posiblemente la resulta de los cuellos de botella genéticos y efectos fundadores durante las migraciones de ladera del Holoceno o la corta duración de la temporada de cultivo y temperaturas más frías en las elevaciones más altas (Hensen et al 2012). La baja diversidad genética en las elevaciones más altas tendrá un impacto directo sobre la viabilidad de las primeras poblaciones que migran con el cambio climático.…”
Section: Otra Posibilidad Para Muchas Poblaciones Disyuntas Deunclassified